Localization of sustainable development goals among non-teaching staff in higher education: the status quo dynamics at great Zimbabwe university - Nyambiya, Isaac; Chapungu, Lazarus; Maoela, Malebajoa Anicia (Frontiers in Education, 2024)
Introduction The influence of non-teaching staff on localizing Sustainable Development Goals (SDGs) within universities is underexplored despite its potential significance. This study examines the familiarization with SDGs at Great Zimbabwe University (GZU). Methods The triangulation convergence model of the mixed methods research design was adopted as the strategy for inquiry. The study surveyed 70 randomly selected non-teaching staff from diverse departments and key informant interviews were done with purposively selected non-teaching staff. Secondary data sources were obtained from the information department and the university website for additional details on SDG localisation initiatives. Results The results indicate that the non-teaching staff members at GZU exhibit a moderate familiarity with SDGs, scoring 42.14%. About 42.86% of the employees had engaged with SDGs documents. Interestingly, respondents perceived the institution as well-prepared for SDGs localization, scoring 62.17%. The overall SDGs localization score is 58.5%, with variations between specific SDGs. In particular, SDG 5 (Gender Equality) scores highest, while SDG 14 (Life below Water) is the least localized. The study identifies several obstacles that hinder non-teaching staff from actively contributing to SDG implementation, such as primarily financial constraints followed by lack of awareness, demotivated employees, insufficient training, and a scarcity of SDG materials. Structural challenges within the institution were also observed. Discussion To facilitate the mainstreaming of SDGs issues among non-academic staff activities and initiatives, the study underscores the need for management to play an enabling role and designate focal persons for SDGs to oversee projects’ execution. Overall, this research sheds light on the current status of SDGs familiarization in higher learning institutions and offers insights for enhancing the involvement of non-teaching staff in achieving SDG targets.